Conformity to occupational safety and health regulations in Malaysian small and medium enterprises - Baba, M. Deros; Ahmad Rasdan, Ismail; Jaharah, A. Ghani; Mohd Yusri, Mohd Yusof (Science Publications, 2014)
Regulation on occupational safety and health in Malaysia had evolved from the prescriptive factory and machinery act to a self-regulated occupational safety and health act. However, from the authors’ observation the high standards of occupational safety and health culture that surpass the legal requirement were not widely practiced by Small and Medium Enterprises (SMEs). The two main objectives of this study are: First, first, to identify and determine the level of conformity and second, to investigate the reasons of nonconformity to occupational safety and health act regulation in SMEs involved the chemical industry sub-sectors. The survey questionnaire was distributed to 150 SMEs in chemical industry sub-sectors. Forty one of the survey questionnaires were completed and returned, giving a response rate of 27.3% for the survey. Survey data were analyzed statistically using the SPSS software. The survey results revealed that an overwhelming majority (92.7%) of the respondents from SMEs are likely not conforming to the basic requirement of occupational safety and health act. In addition to this, the survey also found that only 3.1% of the management personnel can be considered competent in terms of knowledge, skill and ability in carrying out occupational safety and health regulation within their respective organization. While, 96.9% of the respondents that participated in the survey can be considered not competent. The authors hope results of this survey could assist the relevant authorities in formulating a better policy and strategy for implementing occupational safety and health in SMEs involved in chemical industry sub-sectors.